Edukasi Literasi Iklim dan Pelatihan Ecobrick Sebagai Upaya dalam Meningkatkan Kesadaran Lingkungan Bagi Anggota PKK Kecamatan Kedungadem - Lestari, Iin Widya; Fatoni, Mohammad; Putri , Nanin Verina Widya; Wijayanti, Riris; Rahmawati, Selvi; Wafiah, Qoniatin; A’yun, Marwah Qurrota (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
Environmental problems are still a big and complicated problem. All groups including educators, communities, and institutions as well as the government actively participate in efforts to maintain and overcome these problems. The purpose of this community service activity is to conduct socialization and education to cadres and PKK members of Kedungadem sub-district and provide Eco brick training in an effort to utilize plastic waste and increase community eco green awareness in processing plastic waste. This activity was carried out by applying socialization, training and evaluation methods. Based on the results of this activity, the socialization activities went well and PKK members also received education about climate literacy. Then proceed with ecobrik training to utilize plastic waste and plastic bottles into useful products such as flower pots, small chairs and others. After the training, we continued with an evaluation by conducting interviews and filling out an activity evaluation questionnaire. Based on these results, the socialization and ecobrick training activities went smoothly and this had an impact on increasing the understanding of PKK cadres regarding the ability and skills in utilizing plastik bottles and household plastic waste..